Bioclimatic Architecture in Warm Climates 2019
DOI: 10.1007/978-3-030-12036-8_15
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo: An Engineered Alternative for Buildings in the Global South

Abstract: Bamboo is the only Graminea adapted to the life as forest. Bamboos can be found around the globe and are naturally occurring in Africa, America, and Asia in tropical, subtropical and warm temperate areas around the equator. Bamboo are giant grasses that propagate rapidly by the expansion of underground rhizomes. In general, bamboos are known for their rapid growth with a rate of up to 25cm/day in certain species of woody bamboos such as Guadua angustifolia Kunth (Bamboo). Although there are some species of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The use of bamboo as a building material has a long history in the Philippines. Particularly in regions with naturally occurring bamboo forests, such as Africa, America, and Asia [6], bamboo has traditionally been used for housing. Bamboo displays high tensile strength and elasticity [7] while also being a relatively lightweight material, resulting in a high strength-to-weight ratio.…”
Section: Bamboo In Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of bamboo as a building material has a long history in the Philippines. Particularly in regions with naturally occurring bamboo forests, such as Africa, America, and Asia [6], bamboo has traditionally been used for housing. Bamboo displays high tensile strength and elasticity [7] while also being a relatively lightweight material, resulting in a high strength-to-weight ratio.…”
Section: Bamboo In Constructionmentioning
confidence: 99%
“…Their results indicate that further processing bamboo poles into engineered products approximately doubles the initial emissions [19]. Moreover, social housing solutions using different construction materials in Colombia have found that traditional bamboo and EBPs outperform more industrialized building materials, with CBF construction slightly outperforming EBPs for single-story buildings [6]. A parametric LCA approach was developed by Eleftheriou et al [20] to examine the influence of various building parameters, such as building dimensions, on the overall environmental impact.…”
Section: Lca and Bamboomentioning
confidence: 99%
“…With the improvement of living standards, the demand for environmentally friendly, lightweight, and safe structures has increased dramatically [1][2][3][4][5]. Bamboo as a sustainable alternative to traditional building materials, including wood, has started to gain attention [6][7][8][9][10][11][12][13][14][15] due to its short time to harvest [16,17], the variety of species, as well as the high yield, and the ability to reach a maximum height of 15-30 meters in 2-4 months, and the maximum strength in 3-8 years [18,19]. According to life-cycle assessment (LCA) results, bamboo is included in the "factor 20", which means that its impact on the environment is 20 times less compared to modern alternatives [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, interest in bamboo as a building material is growing due to its sustainable characteristics [1][2][3][4][5][6]. Compared to wood, bamboo can grow up to 30 meters in 4 months and reach maximum strength in 3-8 years, which ensures fast and high yield [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%